EFFECT OF PHYLLOSILICATES ON FLUID-ASSISTED HEALING OF GOUGE-BEARING FAULTS - Bos B.; Spiers C.J. (My University, 2000)
On the basis of both experimental and field studies, it is widely accepted that solution transfer processes are important in controlling fault strength recovery (healing) in the hydrothermal reaches of the seismogenic zone. Fluid-assisted healing of fault gouge may be strongly influenced by phyllosilicate content and spatial arrangement, but little is known about such effects. To study these effects, we have performed slide-hold-slide experiments using simulated faults containing gouges of halite+kaolinite saturated with brine. In this system, solution transfer processes are extremely fast. The results show rapid healing in the case of pure halite gouge, whereas almost no such effects were observed in foliated, clay-bearing gouge under otherwise identical conditions. The degree of healing increased with increasing shear strain in monomineralic gouge, whereas the opposite was observed in clay-bearing gouge. The above effects are interpreted to be due to phyllosilicates inhibiting halite-halite grain contact healing processes, an effect which becomes more prominent as on-going shear deformation leads to foliation development. The results raise questions regarding recent application of laboratory-derived healing data for monomineralic gouge to natural fault rocks, since these generally contain significant amounts of phyllosilicates and are often foliated.
Keywords: FAULTS; FRICTION; EARTHQUAKES; FLUIDS PHASE; SHEET SILICATES